2019
DOI: 10.1002/ddr.21544
|View full text |Cite
|
Sign up to set email alerts
|

Identification of embelin, a 3‐undecyl‐1,4‐benzoquinone from Embelia ribes as a multitargeted anti‐Alzheimer agent

Abstract: Beta-secreatse (BACE-1) and cholinesterases are clinically validated targets of Alzheimer's disease (AD), for which natural products have provided immense contribution.The multifaceted nature of AD signifies the need of multitargeted agents to tackle this disease. In the search of new natural products as dual BACE-1/cholinesterase inhibitors, a library of pure natural products was screened for inhibition of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and BACE-1. The screening efforts have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…A fluorescence β-Secretase (BACE-1) Activity Detection Kit was purchased from Sigma–Aldrich and used to determine the effect of the synthesized flavone derivatives on β-secretase activity. The assay was carried out according to the manufacturer’s protocol as described earlier [ 47 , 48 ]. The enzyme solution was reacted with the substrate (7-methoxycumarin-4-acetyl-(Asn670, Lue671)-amyloid β/A4 precursor protein 770 fragment 667–676-(2,4-dinitrophenyl))Lys-Arg-Arg amide trifluoroacetate salt and sulfated polysaccharide samples in a fluorescence assay buffer in different wells.…”
Section: Methodsmentioning
confidence: 99%
“…A fluorescence β-Secretase (BACE-1) Activity Detection Kit was purchased from Sigma–Aldrich and used to determine the effect of the synthesized flavone derivatives on β-secretase activity. The assay was carried out according to the manufacturer’s protocol as described earlier [ 47 , 48 ]. The enzyme solution was reacted with the substrate (7-methoxycumarin-4-acetyl-(Asn670, Lue671)-amyloid β/A4 precursor protein 770 fragment 667–676-(2,4-dinitrophenyl))Lys-Arg-Arg amide trifluoroacetate salt and sulfated polysaccharide samples in a fluorescence assay buffer in different wells.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were assayed in triplicate, and bioactivity was reported with SEM. The method was as described earlier [ 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…In vivo CCl₄ induced ↓LPO, AST, ALT, ALP, LDH, GGT; ↑SOD, CAT, GSH, GPX, GST [137] In vivo TAA ↑Survival, Liver fibrogenesis; ↓Necrosis, Apoptosis HICR [138] T A B L E 1 (Continued) In vivo IRIBI induced ↑La, HLT, GST; ↓BWL, LPO [140] In vivo ICV STZ induced ↓IL-1 β, IL-6, and TNF-α [141] In vivo PTZ induced ↓CCL2 mRNA, IL-1 mRNA, INF-γ mRNA [142] In vivo CUS induced ↓IL-6, TNF-α, IL-1β, COX-2, NO, TBARS [92] In vivo apomorphine induced ↓CI, SC, BDL, NA, SERT [143] In vivo CUS induced ↑BDNF, AO; ↓IL-6, TNF-α, IL-1β, COX-2 [92] In vivo SIA induced ↑RIMR, IR, BDNF, CREB1, SOD1, CAT [144] In vivo CCH induced ↓SMI, SPI; ↑BDNF, CREB1, APP, MAPT, SOD1, NF-κB mRNA [145] Alzheimer's disease in vitro SH-SY5Y ↓Cell viability, Cell proliferation [146] Obesity In vivo HFD induced ↓BW, BP, VFP, SLL, CAR, AGI TBARS ↑SOD, CAT, GSH [88] In vitro ST2, C3H10T1/2 ↓PPAR-γ, C/EBPs, aP2, Adipsin, SCD1, Dkk1, SREBPs, ACC-1, ↑nuclear translocation, TCF-4 [147] In vivo HFD induced ↓BW, Fat, SLT, FFA, TC, GTIR; ↓ALF, Dkk1 [147] Abbreviations: AA, ascorbic acid; AAA, abdominal aortic aneurysm; AADP, albumin anti-denaturation potential; AAI, acetic acid induced; AAIW, acetic acid induced writhing; ACC- high potential in the prevention and treatment of arthritis. For example, a study showed that embelin repressed inflammation and serum CTX-1 in collagen antibody-induced arthritis in mice, signifying its potential application in battling arthritis.…”
Section: Diabetesmentioning
confidence: 99%
“…[141] Another study reported that embelin hampered the development of amyloid-β oligomers by downregulating β-secretase 1 (BACE-1); enhanced cholinergic-transmission by downregulation of acetylcholinesterase (AChE)/butyrylcholinesterase (BChE) and upsurged amyloid-β clearance by P-gp activation. [146] Besides, a study reported neuroprotective and anti-Alzheimer's property of embelin in chronic cerebral hypoperfusion (CCH) model. In this model, administration of embelin markedly protected synaptic plasticity damage and enhanced expression of brainderived neurotrophic factor (BDNF), cAMP response element-binding protein1 (CREB1), amyloid precursor protein (APP), microtubuleassociated protein tau (MAPT), SOD1, and NF-κB mRNA levels triggered by chronic cerebral hypoperfusion rats.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%